1995
DOI: 10.1002/art.1780380309
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for clinical trials in systemic sclerosis (scleroderma)

Abstract: Objective. To develop guidelines for therapeutic trials designed to improve the overall course of systemic sclerosis (SSc), that is, to reduce the development of significant organ damage or death.Methods. A committee developed general guidelines for patient inclusion and exclusion criteria, randomization, blinding of patients and physicians, controls, duration of the trial, investigator training, responses, samples size, study dropouts, statistical analyses, data management, and safety monitoring. Delphi and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0
2

Year Published

1997
1997
2007
2007

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 109 publications
(34 citation statements)
references
References 17 publications
0
32
0
2
Order By: Relevance
“…Previous studies yielding negative results have hampered the development of validated assessment tools that are sensitive to change over the time course of a therapeutic clinical trial. There is continued interest in this area, and several groups of investigators have reported guidelines for disease assessment and for the performance of clinical trials (16,17,31). At present, for a short-term study, the MRSS remains the most frequently used tool for the assessment of skin sclerosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies yielding negative results have hampered the development of validated assessment tools that are sensitive to change over the time course of a therapeutic clinical trial. There is continued interest in this area, and several groups of investigators have reported guidelines for disease assessment and for the performance of clinical trials (16,17,31). At present, for a short-term study, the MRSS remains the most frequently used tool for the assessment of skin sclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…To enrich the study cohort for patients in the progressive phase of dcSSc, the following inclusion criteria were 324 DENTON ET AL required for any study subject: enrollment within 18 months of the onset of their disease (defined as the time from the first non-Raynaud's phenomenon manifestation); a modified Rodnan skin thickness score (MRSS) between 10 and 28 (inclusive); and evidence of worsening disease by any of the following 3 criteria: progression of skin disease to a new skin score site within the previous 3 months; an increase in the skin score from 1 to 3 at any skin score location; or the presence of tendon friction rubs at 3 or more joints (16). The clinical features of the study cohort are given in Table 2.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Diffuse cutaneous SSc was defined as skin involvement on the extremities proximal to the elbows or knees, or truncal involvement. Disease onset was defined as the time of the first symptom clearly attributable to SSc, which included Raynaud's phenomenon (22).…”
Section: Methodsmentioning
confidence: 99%
“…Many reports have attributed improvement in skin thickening to certain medications, but controlled trials have not confirmed these observational studies (8,9). Several problems have made clinical therapeutic trials in scleroderma particularly difficult to perform and interpret, although recent guidelines for the treatment of scleroderma have been made by a National Institutes of Health panel (10). Great variability in the disease makes it hard to identify an adequate number of patients with similar disease features.…”
mentioning
confidence: 99%